Proposed upgarding existing design for Sup Adabi Restaurant at A-G-10 & A-G-11, Jalan SS 6/5A Kelana Jaya, 47301 Petaling Jaya, Selangor / Zarith Anis Jamaludin - Jamaludin, Zarith Anis (Faculty of Architecture, Planning and Surveying, 2007)
The proposal of a new design scheme for the Sup Adabi Restaurant in Kelana Square, Selangor brings together the aim to come out with a more systematic and functional planning for each area with out abandon all the guests’ necessities and services. At the same time, Sup Adabi Restaurant also brings along its objective to create a new attraction and profitable hospitality facility to their customers. Another objective for this proposal is to transform the existing interior which is unattractive to a new fresh look, attractive and dynamic but still maintaining the corporate image of Sup Adabi Restaurant. Therefore, the customers will be enjoying the delicacies as well as its interior environment which is applying the image of Organic blended with Malay Traditional. This three-storey building which taking two shop lots is 9360 square feet and excellent enough to create a great atmosphere for the restaurant and provide spaces to entertain the customers while they having their delicacies in this restaurant. As the conclusion for the whole research which had been carried out from the beginning, is that the design for the Sup Adabi Restaurant will not only provide a village atmosphere for the restaurant, but also able to function for its guest in term of design as well as its services.